Kurds in Turkey ethnographies of heterogeneous experiences - Drechselová, Lucie; Çelik, Adnan, 1983- (Kurdish societies, politics, and international relations., 2019)
This ethnographic volume features fresh research by junior scholars of contemporary Kurdish studies. The contributions are assembled around four themes: women's participation, paramilitary, space, and infrapolitics of resistance.